Honorary Doctorate Dr. H. C. Adriaan van Dis 11th May 2022 - De Vereeniging in Nijmegen - van Dis, Adriaan (Radboud University Press, 2022)
On Wednesday 11th May 2022, Adriaan van Dis received an honorary doctorate from Radboud University for his achievements as an ambassador for language and culture learning. This publication includes the eulogy of the honorary doctorate and the speech of thanks by our honorary doctor. As a writer, commentator and documentary maker, Adriaan van Dis argues for more literacy, and especially for reading stories, poems and comics. Reading stimulates the imagination, promotes empathy and strengthens our tolerance. Rector Magnificus Han van Krieken: ""With this honorary doctorate, Radboud University emphasises the importance of language and cultural studies for society. Like no other, Van Dis stands for the connection between literacy, diversity and inclusiveness."" The now much-praised speech 'Open your mind to other cultures' argues that the humanities are essential for society. This starts with the knowledge of each other's small and large histories and the understanding that words matter in our intercultural communication.